Identification of Novel Genes Mediating Survival of Salmonella on Low-Moisture Foods via Transposon Sequencing Analysis - Jayeola, Victor; McClelland, Michael; Porwollik, Steffen; Chu, Weiping; Farber, Jeffrey; Kathariou, Sophia (Frontiers in Microbiology, 2020)
Salmonella enterica is the leading foodborne pathogen associated with outbreaks involving low-moisture foods (LMFs). However, the genes involved in Salmonella’s long-term survival on LMFs remain poorly characterized. In this study, in-shell pistachios were inoculated with Tn5-based mutant libraries of S. Enteritidis P125109, S. Typhimurium 14028s, and S. Newport C4.2 at approx. 108 CFU/g and stored at 25oC. Transposon sequencing analysis (Tn-seq) was then employed to determine the relative abundance of each Tn5 insertion site immediately after inoculation (T0), after drying (T1) and at 120 days (T120). In S. Enteritidis, S. Typhimurium and S. Newport mutant libraries, the relative abundance of 51, 80, and 101 Tn5 insertion sites, respectively, was significantly lower at T1 compared to T0, while in libraries of S. Enteritidis and S. Typhimurium the relative abundance of 42 and 68 Tn5 insertion sites, respectively, was significantly lower at T120 compared to T1. Tn5 insertion sites with reduced relative abundance in this competition assay were localized in DNA repair, lipopolysaccharide biosynthesis and stringent response genes. Twelve genes among those under strong negative selection in the competition assay were selected for further study. Whole gene deletion mutants in ten of these genes, sspA, barA, uvrB, damX, rfbD, uvrY, lrhA, yifE, rbsR, and ompR, were impaired for individual survival on pistachios. The findings highlight the value of our combined mutagenesis and sequencing strategy to identify novel genes important for the survival of Salmonella in low-moisture foods.